Raindrop size distribution characteristics in summer of a nival glacial zone in eastern Tianshan, Central Asia - Chen, Puchen; Li, Zhongqin; Wang, Puyu; Yang, Min; Jia, Yufeng; Peng, Jiajia (Frontiers in Earth Science, 2022)
Precipitation is a key component of the hydrological cycle, which is critical to understanding its formation and evolution. In this study, based on the observation data of the PWS100 located at the meteorological observation site at the terminal of Urumqi Glacier No. 1, eastern Tianshan Mountains, the statistical characteristics of the summer raindrop size distribution (DSD) were analyzed, and the DSD characteristics of five different rainfall rates(R) and two rainfall types (convective and stratiform) were investigated for the daytime and nighttime. The average raindrop spectral width was the largest in class III (1 < R < 5 mm h−1). The result showed that the raindrop concentration increased with the rainfall rate. The maximum raindrop concentration was at class IV (5 < R < 10 mm h−1), when the raindrop diameter was higher than 1.74 mm. The small and medium size raindrops played a dominant role in precipitation composition in the head watershed of the Urumqi River, contributing 98% of the total raindrop. The convective precipitation at the headwaters was divided into continental clusters. The stratiform/convective Dm-log10Nw was characterized by a large mass-weighted mean diameter Dm = 1.523/2.608, and a generalized intercept log10Nw = 2.841/3.469. N(D) of convective precipitation was significantly different between the daytime and nighttime, while that of stratiform precipitation was almost the same. The constraint relationship between R-Dm and R-log10Nw of these two precipitation types was deduced, the exponent of the R-log10Nw relationship of the two precipitation types was negative, and the Dm value of stratiform precipitation tended to be stable at a higher rainfall rate (1–2 mm). Finally, we deduced the power-law relationship between radar reflectivity (Z) and rain rate (R) [Z = A*Rb] for stratiform and convective precipitation at the headwaters. Z = 698.8R2.0 was for stratiform, and Z = 47.1R2.0 was for convective. These results, for the first time, offer insights into the microphysical nature of precipitation in the head watershed of the Urumqi River during the summer and provide essential information that could be useful for precipitation retrievals based on weather radar observations.